Forearm-Based Ulnar Gutter versus Hand-Based Thermoplastic Splint for Pediatric Metacarpal Neck Fractures: A Blinded, Randomized Trial. Issue 3 (March 2016) - Davison, Peter G.; Boudreau, Nicole; Burrows, Ruth; Wilson, Kenneth L.; Bezuhly, Michael
Abstract : Background: Use of a hand-based thermoplastic splint for treatment of isolated fifth metacarpal neck fractures in pediatric patients has not previously been studied in a randomized blinded trial. Methods: The authors conducted a blinded, 1:1 allocation, two-arm parallel group, superiority design, randomized controlled trial in patients aged 16 years or younger with isolated fifth metacarpal neck fractures. Patients were immobilized for 3 weeks in a conventional forearm-based ulnar gutter or hand-based thermoplastic splint. Primary outcome was difference in active range of motion between splint groups. Secondary outcomes included fracture union, treatment adherence, grip strength, and patient-reported pain and functional outcomes. Results: Between February of 2013 and August of 2014, 40 patients were enrolled in the trial. No differences were observed in baseline characteristics between groups. Mean range of motion was significantly better in the thermoplastic splint group compared with the ulnar gutter splint group at 3 weeks ( p = 0.048). All patients had full range of motion at 12 weeks. Treatment adherence was 75 percent and 59 percent for ulnar gutter and thermoplastic splint groups, respectively ( p = 0.46). Among ulnar gutter splint patients, decreased grip strength (injured versus noninjured) was observed at 3 and 6 weeks, and was significantly weaker compared with thermoplastic splint patients ( p = 0.01). Reported pain scores were similar between groups. Patient-reported functional outcome scores were similar between groups at each time point. No nonunions were observed at 12 weeks. Conclusion: In pediatric patients, hand-based thermoplastic splints resulted in improved early range of motion and grip strength, with no increased pain, nonadherence, or complications compared with conventional ulnar gutter splints. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, I. Abstract : Supplemental Digital Content is available in the text.